Predictors of acupuncture referral for chronic non-specific low back pain among medical practitioners in Malaysia - Sim, Sze Kiat; Md Mizanur, Rahman; Wong, Hon Foong (Malaysian Medical Association, 2025)
Introduction: Chronic non-specific low back pain (cnLBP) is a common primary care health issue. While acupuncture offers promising potential as a complementary treatment, its acceptance and integration into standard medical care for cnLBP remains inconsistent. This study investigated the predictors of acupuncture referral for cnLBP using the Theory of Planned Behaviour (TPB).